Hubungan Tingkat Pengetahuan Dengan Perilaku Penggunaan Antibiotika Di Kembangan Jakarta Barat - ., Teodhora (LPPM Akademi Farmasi Imam Bonjol Bukittinggi, 2023)
Infectious diseases are still among the top ten most common diseases in Indonesia. Antibiotics are drugs that are often used to treat this problem. Irrational use of antibiotics will increase antibiotic resistance. This study aims to determine the relationship between the level of knowledge with the behavior of using antibiotics. This type of research is descriptive analytical research that is quantitative in nature using observational methods with cross sectional design. The research was conducted in the area of RT 03 RW 010, Kembangan Utara Village, Kembangan District, West Jakarta City, with a research population of 420 people. The sampling technique used the Slovin formula, so that the total number of respondents was 91 respondents. The data analysis used is univariate and bivariate analysis. The results of the chi-square test showed that there was a significant relationship between age and last education on the level of knowledge with a p- value <0.05. There is a significant relationship between the level of knowledge and the behavior of using antibiotics where the correlation coefficient test results show a significant relationship in the direction of the p-value of 0.004 and the direction of the positive correlation of 0.302.